Aquisição da sintaxe do português europeu como língua materna: ponto da situação - Lobo, Maria; Santos, Ana Lúcia (Revista da Associação Portuguesa de Linguística, 2022)
This paper establishes a broad state-of-the-art of the research on the acquisition of the syntax of European Portuguese. It identifies broad questions that are subject to debate, the main topics and lines of research that have been pursued in the last decades, available resources, and new paths that can be developed.